The adaptation of Silencing the Self Scale for Women into Turkish: The study of validity and reliability - Bozkur, Binaz (Anales de Psicología / Annals of Psychology, 2023)
Objective: Self-silencing is a variable associated with psychological disorders in women, especially with depression. The aim of this study is to test the psychometric properties of the Turkish form of the Self-Silencing Scale and to enable the scale to be used in the field of mental health. Method: 560 women, aged from 18 to 59, enrolled in the study. Results: First and higher order confirmatory factor analyzes (CFA) revealed sufficient goodness of fit values ​​for the four-factor structure of the scale. It was observed that the values ​​obtained from the Cronbach’s Alpha and test-retest reliability studies of the scale were also within acceptable limits. Discussion: Evidence was reached that the scale which adapted to Turkish within the scope of the study is a valid and reliable measurement tool. These results show that the scale has a counterpart in Turkish culture and indicates a similar structure and can be used in future studies.